2014
DOI: 10.1002/pds.3709
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chats on French internet forums about drugs and pregnancy

Abstract: This study shows that information related to drugs and pregnancy in online chats could be at risk for pregnant women. Internet users must be aware that online forums are not reliable sources of information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
(18 reference statements)
0
17
0
1
Order By: Relevance
“…(), Lupattelli, Spigset, and Nordeng (), Palosse‐Cantaloube et al. (), Sinclair et al. (), Hämeen‐Anttila et al.…”
Section: The Studyunclassified
“…(), Lupattelli, Spigset, and Nordeng (), Palosse‐Cantaloube et al. (), Sinclair et al. (), Hämeen‐Anttila et al.…”
Section: The Studyunclassified
“…This is the first study to systematically review a large number of posts published publicly on multiple social media platforms related to the safety of medication use during pregnancy. Two previous studies focussed on a single social media source only: chats on French forums 14 and English YouTube videos. 15 Similar to those studies, we observed low concordance between the perceived online safety and official ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Using social media as a data source for pharmacoepidemiological research or pharmacovigilance is challenging due to technical, regulatory and ethical issues . In a 2014 study, a limited number of chats on French forums was analysed to assess the quality and reliability of information on medication use in pregnancy shared by Internet users . Likewise, Hansen et al reported on YouTube videos as a source of information on medication use during pregnancy in 2016 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that the underlying mechanism has only recently elucidated in 2014, several decades later (11). A further issue is that the relationship between patient and physician in the Internet age is complicated by the reliance of the former on untrustworthy data or unfounded skepticism of new untried developments (12, 13). …”
Section: Why the Progress In The Development Of Therapeutics In Feto-mentioning
confidence: 99%